Controlling procesowo-funkcjonalny w przedsiębiorstwie handlowo-usługowym sektora energetycznego : wykorzystywane narzędzia oraz rozwiązania organizacyjne - Stępniak, Sławomir (Process Function Controlling in Trade and Service Company Operating in Energy Industry : Tools Applied and Organizational Solutions, 2007)
The paper depicts a set of different tools and solutions which can be applied in a company operating in a energy industry. The main emphasis is put on controlling-oriented applications with respect to functional and process view.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 471-485